Level of knowledge of basic life support: from layperson to health professional. An integrative review (Research, Society and Development, 2023)
Introduction: Basic Life Support (BLS) is a set of emergency procedures that aim to maintain the respiratory and cardiac functions of a person who has suffered a cardiorespiratory arrest (CRA) until specialized medical help arrives. These techniques include performing cardiopulmonary resuscitation (CPR) maneuvers, which involve chest compressions, ventilations, airway clearance, oxygen administration, and defibrillation. Objective: The main objective of this study is to carry out an integrative review of the level of knowledge of the layman to the health professional about basic life support. Methodology: Descriptive bibliographic review in an exploratory character with a qualitative approach, based on scientific publications found in PUBMED, SCIELO and Google Scholar databases. Results: The study had a sample of 9 articles, of which the level of knowledge of basic life support was cited in all articles. Discussion: It revealed a worrying situation, with most people feeling incapable of acting in emergencies. Conclusion: It is essential that there is training of the general population on basic life support, thus ensuring a lower morbidity and mortality rate.